Surveillance Strategies for Hepatocellular Carcinoma: Recent Advances and the Shifting Paradigm - DEMİRTAŞ, COŞKUN ÖZER; GÜNDÜZ, FEYZA; ÖZDOĞAN, OSMAN CAVİT (SPRINGER, 2021)
Currently, international liver societies recommend screening at-risk individuals for HCC (patients with cirrhosis regardless of etiology, and/or chronic hepatitis B virus, and/or advanced liver fibrosis) with biannual abdominal ultrasound (USG) with or without alpha-fetoprotein (AFP). The global acceptance of USG in surveillance relies on the absence of risks, non-invasiveness, and lower costs. However, the suboptimal performance of USG +/- AFP in reaching direct and indirect goals of HCC surveillance highlights the need for alternative surveillance strategies. Several studies targeted contrast-enhanced magnetic resonance imaging techniques, but the main barriers for their entrance to surveillance programs have been concerns about cost-effectivity and long scan times. Overall, the HCC risk stratification appears at hand by several validated multiple score systems, but their optimal performance is obtained only in populations who show highly homogenous clinical, pathological, epidemiologic, etiologic, and therapeutic characteristics, and this limitation poses a major drawback to their sustainable use in clinical practice. We need globally validated and molecular integrated risk stratification tools to shape the future tailored HCC surveillance decision algorithms. A dynamic process for HCC surveillance algorithms awaits us owing to the expected further prospective studies focusing on risk-stratified screening strategy.
Keywords: Hepatocellular carcinoma; Surveillance; Risk assessment; Ultrasound; Magnetic resonance imaging; RISK INDEX; GROWTH-RATE; CIRRHOSIS; CANCER; VALIDATION; STAGE